Treating acute fatty liver of pregnancy with artificial liver support therapy: Systematic review. Issue 38 (September 2018) - Wu, Zhenping; Huang, Peng; Gong, Yi; Wan, Junhui; Zou, Wei
Abstract: Background: Acute fatty liver of pregnancy (AFLP) is a serious disease with high mortality. Recent data suggest that postpartum application of artificial liver support therapy (ALST) in AFLP management improves disease outcome. In current study, we tend to further evaluate whether the type, the timing, and the number of postpartum ALST sessions and other clinical factors including complications and liver and renal function will influence disease outcome in ALST era. Methods: Medical records of 15 AFLP patients having postpartum ALST in our hospital from 2010 to 2016 were first retrospectively reviewed. A systematic review and statistical analysis was then conducted with our cases and those having postpartum ALST reported in PubMed, Embase, Cochrane, and ClinicalTrials.gov till the end of June 2016. Results: Nine relevant studies were identified in the public databases. A total of 104 cases were enrolled for analysis including 15 cases from our hospital and 89 cases from the identified 9 studies. Univariate analysis revealed that 2 complications, postpartum hemorrhage and multiple organ dysfunctions (MODS), were associated with the outcome of AFLP patients undergoing postpartum ALST. Binary logistic regression analysis further indicated that MODS was the only independent factor affecting disease outcome. Surprisingly, factors including pre-ALST serum levels of total bilirubin and creatinine, the type and number of postpartum ALST sessions, time interval between delivery and ALST were unrelated to disease outcome. Conclusion: Current data suggest that postpartum ALST improves the outcome of AFLP patients but more properly designed experiments are needed to confirm this point. Our study further indicates that occurrence of MODS carries a bad prognosis even in ALST era. Our study provides valuable information on guiding the clinical application of postpartum ALST in AFLP management. Abstract : Supplemental Digital Content is available in the text